Storytelling as a Tool for Activist Public Relations: A Qualitative Study in Case of Women - Aytuğ Mermer Üzümlü; Beris Artan Özoran (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This study focuses on storytelling in activist public relations. Stories emerge as an important "activist public relations" tool in non-governmental organizations' social change and awareness-raising efforts. The research aims to investigate both short and long-term effects of storytelling on emotions, awareness levels, and behavioral changes across different age groups. To illustrate the use of storytelling in activist public relations within the cosmetics industry, the researchers selected the short film "Save Ralph," produced by Humane Society International in 2021. The short film tells in an emotional tone, from the mouth of a rabbit, what happened to him during cosmetic experiments. The research, employing a qualitative research design, comprises three stages. Firstly, a survey was conducted among 30 women from various age groups to gather insights into their definitions of cosmetic products, usage frequency, and factors influencing their preferences. In the second stage, participants were shown the selected short film, followed by in-depth interviews. Lastly, follow-up interviews were conducted with the same group of women three months later. The findings revealed that storytelling had the most significant impact on emotions, awareness levels, and behavioral changes among women aged 18-23. This underscores the effectiveness of storytelling as a strategy for driving social change and raising awareness within activist public relations initiatives.